Made in South Africa? An Assessment of Local Content within the Automotive Value Chain - Bowden, Guy (School of Economics, 2023)
Despite rising vehicle production, the South African automotive industry has experienced declining levels of local content in locally produced vehicles. This is partly a result of increasing international competition, worsening factor and overhead costs, and insufficient economies of scale. Prior to the global and national lockdowns prompted by the COVID-19 pandemic, the automotive supply chain had already been under strain for several years. This study examines the evolution of the South African automotive value chain and discusses the key challenges and opportunities facing localisation efforts. The study uses a combination of existing literature, industry reports, time series data and benchmarking data to analyse the development of the industry. The study reaffirms the underdevelopment of the local supply chain and points to its continued decline. The introduction of an amended national automotive industrial programme (the APDP 2) promises to address some of the shortcomings of its predecessor. However, several challenges remain, namely: limited domestic market protection for automotive components; high tax rates on locally produced vehicles; an ineffective transformation policy (BBBEE) that harms small businesses; a managerial leadership and skills shortage among 2nd and 3rd tier firms as well as the broader manufacturing community; and an expensive and dysfunctional national ports system. Without serious structural redress, this study finds that the automotive industry is not poised to meet the target of 60% local content by 2035 as laid out in the South African Automotive Masterplan. Finally, five internal combustion engine vehicle models are identified as having significant potential around which to grow the local supply chain. However, global pressures are driving the transition to electric vehicles at an unprecedented rate. The industry must urgently localise the sourcing and production of new electric vehicle technologies if it is to maintain its role as a leader for industrialisation in South Africa and the Sub-Saharan region.